Leveling the Playing Field: Closing the Gap in Public Awareness of Genetics between the Well Served and Underserved - Kung, Johnny (The Hastings Center report, 2016)
The impact of genetic technologies is being felt in many aspects of society, including medicine and the legal system, as well as the personal lives of individuals. How do we make sure that all segments of the population are equally aware of these technologies and have ample opportunity to voice opinions and shape the future? One ongoing effort, which began ten years ago and in which we are directly involved, is the Personal Genetics Education Project, a nonprofit initiative housed within and largely supported by the Department of Genetics at Harvard Medical School. The goal of pgEd is to raise public awareness and promote conversations about the benefits and implications of the genetics revolution in ways that are inclusive of all voices regardless of socioeconomic, educational, ethnic, cultural, or religious background. This essay describes our approach and experience in hopes that they will be of help to others engaged in similar efforts.